Reasoning game in learning programming / Hakimah Sazali - Sazali, Hakimah (2009)
Computer programming is difficult to be learned and understand especially for novice and weak students. The current method to teach programming is by using book, lecturer and hands-on. Some of student who weak in programming course, dropped out from programming course because they fell bored to learn programming. Study has shown that the number of people who spent more time on playing game is increasing every year. Therefore, the idea of edutainment is very significant in attracting student to study while playing. Game-based learning is one of the modern pedagogical approaches beginning to gain attention in education. This project integrated multimedia element application to make learning process more fun and effective for students. The purpose is to provide to better way of learning selection and repetition structure for student and easy for student to be learn and understand by develop reasoning game in learning selection and repetition structure. This research has come out with game that will provide platform for novice or weak student in learning the subject. For the time being, the project only focuses on selection and repetition structure.